Reaction of the decaosmium carbido cluster [Os₁₀(µ₆-C)(CO)₂₄]²⁻ with halostibines - Barik, Chandan Kr (2022)
The dianionic cluster [Os10(µ6-C)(CO)24]2− reacts with excess SbX3 or p-tolylSbX2 to form the monoanionic clusters [Os10{µ4-Sb(p-tolyl)nX2-n}(µ6-C)(CO)24]− (n = 0; X = Cl, I; n = 1, X = Cl) via insertion into an Os–Os bond. Further insertion into an Os–Os bond occurs when they are reacted further with excess iodine. The chemistry and structure of these clusters can be understood in terms of the isolobal analogy between [Sb(p-tolyl)nX2-n)]+ and I+.